A bevy of area-preserving transforms for map projection designers. Issue 3 (4th May 2019) - Strebe, Daniel "daan"
ABSTRACT: Sometimes map projection designers need to create equal-area projections to best fill the projections' purposes. However, unlike for conformal projections, few transformations have been described that can be applied to equal-area projections to develop new equal-area projections. Here, I survey area-preserving transformations, giving examples of their applications and proposing an efficient way of deploying an equal-area system for raster-based Web mapping. Together, these transformations provide a toolbox for the map projection designer working in the area-preserving domain.